CURRICULUM DEVELOPMENT MODEL FOR RENEWAL OF ISLAMIC BOARDING SCHOOLS AND MADRASAH EDUCATION - Faradila, Aulia (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This article discusses the renewal of pesantren and madrasah education with a focus on a comparison of curriculum development models. There are four models discussed, namely the Rogers model, Ralph Tyler, Robert S. Zais, and the model of Muslim scholars consisting of al Ghazali, al Farabi, Ibn Sina, Ibn Khaldun, and Ibn Rusydi. This article aims to discuss the advantages, disadvantages, and critical discussion of each of these curriculum development models. The research method used is literature study with descriptive and critical analysis techniques. The results of the analysis show that each model has advantages and disadvantages, as well as differences in the basic concepts of curriculum development. However, Ralph Tyler's model is considered the most consistent and flexibly applicable model. It is hoped that this article can provide a better understanding of the renewal of Islamic boarding schools and madrasah education through curriculum development, as well as provide guidance for future Islamic education curriculum development.